Dietary Patterns in Portuguese Children and Adolescent Population: The UPPER Project - de Moraes, MM (2021)
Considering the nature, extent, and purpose of food processing, this study aims to identify dietary patterns (DPs) and their associations with sociodemographic factors and diet quality in Portuguese children and adolescents. Cross-sectional data were obtained from the National Food, Nutrition and Physical Activity Survey (20152016) of the Portuguese population. Dietary intake was obtained from two non-consecutive days and food items were classified according to the NOVA system. The proportion (in grams) of foods in the total daily diet was considered to identify DPs by latent class analysis, with age and sex as concomitant variables. Associations of DPs with sociodemographic characteristics were assessed using multinomial logistic regression. Linear regressions adjusted by sociodemographic characteristics tested associations of DPs with diet quality. DPs identified were: Unhealthy (higher sugar-sweetened beverages, industrial breads, and sausages intake), Traditional (higher vegetables, fish, olive oil, breads, ultra-processed yogurts, and sausages intake), and Dairy (higher intake of milk, yogurt, and milk-based beverages). Unhealthy was associated with older ages and lower intake of dietary fibre and vitamins and the highest free sugars and ultra-processed foods (UPF), although all DPs presented significant consumption of UPF. These findings should be considered for the design of food-based interventions and school-feeding policies in Portugal.